Evaluation of fungicides and application timings for control of Fusarium head blight of winter wheat in Georgetown, DE, 2025 - Shiv Singla; Alyssa K. Betts (Plant Health Progress, 2026)
Fusarium head blight (FHB), primarily caused by Fusarium graminearum, is a devastating disease of wheat (Triticum aestivum L.) worldwide. It results in bleached heads and shriveled, mycotoxin-contaminated, tombstone-shaped grain, reducing both yield and grain quality. This report evaluated fungicide efficacy and application timing for FHB management in soft red winter wheat ‘Shirley’ in Georgetown, Delaware, in 2025. Disease incidence and severity, Fusarium-damaged kernels, yield, and deoxynivalenol levels were evaluated for all treatments. Results from these trials will help advise U.S. wheat growers in developing effective FHB management strategies to reduce yield losses and mycotoxin contamination in wheat.